Evaluation of hydrogel matrices for vessel bioplotting: Vascular cell growth and viability - Singh, Raminder; Sarker, Bapi; Silva, Raquel; Detsch, Rainer; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Cicha, Iwona (Journal of Biomedical Materials Research Part A, 2015)
Developing matrices biocompatible with vascular cells is one of the most challenging tasks in tissue engineering. Here, we compared the growth of vascular cells on different hydrogels as potential materials for bioplotting of vascular tissue. Formulations containing alginate solution (Alg, 2%, w/v) blended with protein solutions (silk fibroin, gelatin, keratin, or elastin) at 1% w/v were prepared. Human umbilical vein endothelial cells (ECs), smooth muscle cells (SMCs), and fibroblasts were cultivated on hydrogels for 7 days. Cell number and morphology was visualised using fluorescent staining at day 3 and 7. Cell metabolic activity was analysed using WST assay. Compared to pure Alg, Alg/keratin, Alg/gelatin and Alg/silk fibroin provided superb surfaces for ECs, supporting their attachment, growth, spreading and metabolic activity. SMCs showed best colonization and growth on Alg/silk fibroin and Alg/keratin hydrogels, whereas on elastin-containing hydrogels, cell clustering was observed. Fibroblasts growth was enhanced on Alg/elastin, and strongly improved on silk fibroin- and keratin-containing hydrogels. In contrast to the previous studies with alginate dialdehyde-gelatin crosslinked gels, Alg/gelatin blend hydrogels provided a less favourable scaffold for fibroblasts. Taken together, the most promising results were obtained with silk fibroin- and keratin-containing hydrogels, which supported the growth of all types of vascular cells.
Keywords: alginate-protein hydrogels; biocompatibility; fibroblasts; scaffold endothelialisation; smooth muscle cells